Characterization of concurrent target suppression by JNJ-61178104, a bispecific antibody against human tumor necrosis factor and interleukin-17A. Issue 1 (1st January 2020) - Zheng, Songmao; Shen, Fang; Jones, Brian; Fink, Damien; Geist, Brian; Nnane, Ivo; Zhou, Zhao; Hall, Jeff; Malaviya, Ravi; Ort, Tatiana; Wang, Weirong
ABSTRACT: Tumor necrosis factor (TNF) and interleukin (IL)-17A are pleiotropic cytokines implicated in the pathogenesis of several autoimmune diseases including rheumatoid arthritis (RA) and psoriatic arthritis (PsA). JNJ-61178104 is a novel human anti-TNF and anti-IL-17A monovalent, bispecific antibody that binds to both human TNF and human IL-17A with high affinities and blocks the binding of TNF and IL-17A to their receptors in vitro . JNJ-61178104 also potently neutralizes TNF and IL-17A-mediated downstream effects in multiple cell-based assays. In vivo, treatment with JNJ-61178104 resulted in dose-dependent inhibition of cellular influx in a human IL-17A/TNF-induced murine lung neutrophilia model and the inhibitory effects of JNJ-61178104 were more potent than the treatment with bivalent parental anti-TNF or anti-IL-17A antibodies. JNJ-61178104 was shown to engage its targets, TNF and IL-17A, in systemic circulation measured as drug/target complex formation in normal cynomolgus monkeys (cyno). Surprisingly, quantitative target engagement assessment suggested lower apparent in vivo target-binding affinities for JNJ-61178104 compared to its bivalent parental antibodies, despite their similar in vitro target-binding affinities. The target engagement profiles of JNJ-61178104 in humans were in general agreement with the predicted profiles based on cyno data, suggesting similar differences in the apparent in vivo target-binding affinities. These findings show that in vivo target engagement of monovalent bispecific antibody does not necessarily recapitulate that of the molar-equivalent dose of its bivalent parental antibody. Our results also offer valuable insights into the understanding of the pharmacokinetics/pharmacodynamics and target engagement of other bispecific biologics against dimeric and/or trimeric soluble targets in vivo .